Effect of organic media and seaweed extracts (seaweed - Fe) on the vegetative growth and flowering of Narcissus tazetta plant cv. Khatini - Khushaba, Ban Gbraeel; Abdulrahman, Yousif Ali (Sulaimani Journal for Pure and Applied Sciences, 2018)
A pot experiment has been carried out in College of Agriculture at Horticulture department nursery. Duhok University during the period from Oct., 1, 2015 to Apr., 1, 2016, to investigate the effect of three different organic media (Sheep manure + loam (3:1), poultry manure + loam (3:1) and peat moss + loam (3:1)) as volume and three concentrations of seaweed Fe extract (0, 2 and 3 ml L-1) on the growth and flowering of Narcissus tazetta plant (cv. Khatini). The experiment was laid out in Randomized Complete Block Design (RCBD) of three factors in three replicates. The results showed that sheep and poultry manure media were significantly superior to peat moss medium which early in date of sprouting (85.10 and 85.46) days, and to obtain on the best characteristics of vegetative and flowering includes (leaf area, dry weight of leaves, date to flowering and number of florets/stalk flower). Seaweed extract also had a significant effect; this effect was increased with increasing of seaweed extract concentrations to 3 ml L-1 on the growth characters of narcissus plant as compared with 2 ml L-l and control treatment in to accelerate the date of sprouting (85.48 days), gave a significant increase in leaves number. While 2 ml L-l of seaweed extracts was significantly superior on 0 and 3 ml L-1 which accelerates the date of flowering (146.64) days and gave the high length of stalk flowers.
Keywords: Effect of organic media and seaweed extracts seaweed Fe on the vegetative growth and flowering of Narcissus tazetta plant cv Khatini